The Effects of Public Sector Management and Institutions on Economic Growth in Sub-Saharan Africa - Dadzie, P. (University of Ghana, 2023)
Strong Public Sector Management and Institutions (PSMIs) are required for the sustained economic growth and development of countries. However, Sub-Saharan Africa’s (SSA’s) PSMI scores from the World Bank’s Country Policy and Institutional Assessment (CPIA) are relatively weak. Equally weak are the scores of the indices of PSMI, which are Property Rights and Rule-Based Governance, Quality of Budgetary and Financial Management, Efficiency of Revenue Mobilisation, Quality of Public Administration, and Transparency, Accountability and Corruption in the public sector. The study set out to empirically examine the extent to which SSA’s PSMI, and the indices of PSMI, influence its economic growth. The static panel estimation technique was employed for the empirical examination because it gives better results with data from thirty (30) SSA countries from 2005 to 2020. The empirical analyses revealed that PSMI positively influence SSA’s economic growth at 1% significance level in line with the extant literature. The study further revealed that the Quality of Public Administration index exerts the greatest influence in absolute terms on economic growth in SSA. Again, Property Rights and Rule-Based Governance was found to exert the least influence in absolute terms on economic growth in SSA. However, among the five indices of PSMI, only the Efficiency of Revenue Mobilisation’s index was found to correlate positively at 10% significance level with economic growth in SSA. The remaining four indices reported significant negative relationships with economic growth in SSA. The study recommends that SSA governments, development partners and civil society organisations should collaborate to build robust PSMI to achieve sustainable economic growth.
MPhil. Economics
Keywords: Public Sector Management; Sub-Saharan Africa’s (SSA’s); economic growth; development